Potential Carbon Content in The Coastal Mangrove Forests Area Of West Lombok District, West Nusa Tenggara Province - Haryani Haryani; Muhlis Muhlis; Didik Santoso (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Mangrove forests have very important ecological functions for coastal areas as carbon stores so this study aims to determine the potential carbon content of mangrove forests. The implementation of this research is in the coastal area of ​​West Lombok Regency, West Nusa Tenggara Province. Two locations were found, namely Sekotong Beach and Cemara Beach. This research method uses a survey method. Data were analyzed by IPCC analysis method. The results showed that at Cemara Beach the highest carbon content was produced in the mangrove species Avecennia lanata, with the total carbon content and carbon absorption being 7,456 tons C/ha and 27,364 tons CO2/ha. while at Sekotong Beach the carbon content is found in the Avecennia lanata species, with a total carbon content of 2,847.6 tons C/ha and carbon sequestration of 10,067.54 tons CO2/ha. The difference in potential carbon content on the two beaches in West Lombok district is due to because the soil conditions are different but the carbon content is still good enough for the potential carbon content in the coastal mangrove ecosystem area of ​​West Lombok Regency, West Nusa Tenggara.